HOW EDUCATION SHAPES TAX MORALE: EXPLORING THE MEDIATING EFFECT OF INCOME - Iranda, Andy Dwiki; Preacyllia, Abellinda (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
Tax morale is a crucial factor in enhancing taxpayer compliance and the effectiveness of the taxation system. However, previous studies have not clearly explained howeducation influences tax morale. Therefore, this study aims to use income as a mediating variable to explore the pathway by which education impacts tax morale, providing a more comprehensive understanding of this relationship. The population in this research is the entire population of Indonesia in 2017, which was 255 million people. The sampling technique used simple random sampling so that 2,878 people were obtained as samples. This research uses STATA 17 software with partial least squares. The research results show that education has a significant positive effect on income. Education has a significant positive effect on tax morale. Income has a significant positive effect on tax morale. Meanwhile, income can mediate the influence of education on tax morale. These findings suggest that enhancing education can improve both income and tax morale, so future government policies should consider educational initiatives to boost tax compliance. Further research could explore psychological variables and employ experimental approaches to better understand the relationship between education, income, and tax morale.